(untitled) - Mencher, Melvin (Boston, 2006)
Teaching by example through vivid writing, Professor Mencher shows students the fundamentals of reporting and writing news in this new edition of a classic text.
Keywords: Reporters and reporting,Journalism,Nghề viết báo,Tường thuật và người đưa tin; Authorship,Tác giả